2004
DOI: 10.1177/073428290402200402
|View full text |Cite
|
Sign up to set email alerts
|

A Construct Validation Study of Phonological Awareness for Children Entering Prekindergarten

Abstract: The purpose of this study was to determine the psychometric characteristics of a phonological awareness assessment for prekindergarten children using Messick's (1989) framework for unitary construct validity. Upon entry into prekindergarten, children were given rhyme discrimination, syllable segmentation, initial phoneme isolation, and phoneme blending assessments drawn from The Phonological Awareness Test (Robertson & Salter, 1997). Item analyses indicated high internal consistencies, but some tasks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Specifically, there has been a lack of consistency in the methods by which phonemic awareness has been measured, largely because disagreements about the ways that one should evaluate phonemic awareness (Anthony & Lonigan, 2004;Jimenez & Venegas, 2004). That disagreement has, in turn, raised concerns about the influence of different measurement tasks on CLT (Cisero & Royer, 1995;Durgunoglu et al, 1993;Durgunoglu & Roediger, 1987;Everett, Smythe, Ocampo, & Gyarmathy, 2004;Garcia, 1991;Gillon, 2005;Lundberg et al, 1988;Naslund & Schneider, 1996;Stuart-Smith & Martin, 1999;Webb, Schwanenflugel, & Kim, 2004). Fortunately, despite differences in how phonemic awareness is measured, a growing body of empirical studies has found that tasks, like initial sound identification and phoneme segmentation tend to measure one ability or at least highly correlated abilities (Gillon, 2005;Wagner, Torgeson, Rashotte, Hecht, Barker, Burgess, et al 1997).…”
Section: Tasks and Proceduresmentioning
confidence: 99%
“…Specifically, there has been a lack of consistency in the methods by which phonemic awareness has been measured, largely because disagreements about the ways that one should evaluate phonemic awareness (Anthony & Lonigan, 2004;Jimenez & Venegas, 2004). That disagreement has, in turn, raised concerns about the influence of different measurement tasks on CLT (Cisero & Royer, 1995;Durgunoglu et al, 1993;Durgunoglu & Roediger, 1987;Everett, Smythe, Ocampo, & Gyarmathy, 2004;Garcia, 1991;Gillon, 2005;Lundberg et al, 1988;Naslund & Schneider, 1996;Stuart-Smith & Martin, 1999;Webb, Schwanenflugel, & Kim, 2004). Fortunately, despite differences in how phonemic awareness is measured, a growing body of empirical studies has found that tasks, like initial sound identification and phoneme segmentation tend to measure one ability or at least highly correlated abilities (Gillon, 2005;Wagner, Torgeson, Rashotte, Hecht, Barker, Burgess, et al 1997).…”
Section: Tasks and Proceduresmentioning
confidence: 99%
“…Research by Lonigan and colleagues (e.g., Lonigan, 2004a;Lonigan, Burgess, Anthony, & Barker, 1998) and others (e.g., Bowey, 1995;Chaney, 1994;Hecht, Burgess, Torgesen, Wagner, & Rashotte, 2000;Raz & Bryant, 1990;Webb, Schwanenflugel, & Kim, 2004) has shown consistently that preschool and early school age children from lower-income backgrounds and those whose parents have less education demonstrate lower phonological awareness skills than more affluent peers. This discrepancy holds for the other key emergent literacy skills of print knowledge and oral language as well.…”
Section: Why Phonological Awareness Is Important For Later Readingmentioning
confidence: 99%
“…That is, growth in one skill can set the stage for, and increase, improvement in the other. This may be particularly true for the link between letter-sound knowledge and onset-rime and phoneme level phonological awareness skills (e.g., Carroll, 2004;Johnston, Anderson, & Holligan, 1996;Foy & Mann, 2006;Webb et al, 2004). Further, the forthcoming NELP Report (Lonigan et al, in press-a), demonstrates that almost all of the instructional studies to date that yielded significant growth in letter knowledge also included instruction in phonological awareness, and the earlier National Reading Panel Report on phonemic awareness instruction supported the inclusion of letters when teaching phonemic awareness (NRP, 2000).…”
Section: Reciprocal Links With Print Knowledge and Oral Languagementioning
confidence: 99%
See 1 more Smart Citation
“…Anthony et al, 2002). Webb, Schwanenflugel, and Kim (2004) similarly discerned the correlation between phonological skill and later phonemic skill, and their corresponding predictive relationship to alphabetic knowledge.…”
Section: Introductionmentioning
confidence: 92%